2019
DOI: 10.21203/rs.2.10520/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interaction of camel Lactoferrin derived peptides with DNA: a molecular dynamics study

Abstract: Background: Lactoferrampin (LFampin), Lactoferricin (LFcin), and LFchimera are three well-known antimicrobial peptides derived from Lactoferrin and proposed as alternatives for antibiotics. Although the intracellular activity of these peptides has been previously demonstrated, their mode of action is not yet fully understood. Here, we performed a molecular dynamics simulation study to understand the molecular interactions between camel Lactoferrin derived peptides, including CLFampin, CLFcin, and CLFchimera, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…in vitro antibacterial, anti-biofilm and antioxidant activity of the recombinant chimeric peptide were determined on some food spoilage bacterial strains. Finally, using computational modeling approaches we try to predict peptide interaction to lipopolysaccharides (LPS) and DNA as two main targets in bacteria [15,36,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…in vitro antibacterial, anti-biofilm and antioxidant activity of the recombinant chimeric peptide were determined on some food spoilage bacterial strains. Finally, using computational modeling approaches we try to predict peptide interaction to lipopolysaccharides (LPS) and DNA as two main targets in bacteria [15,36,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…The results for all treated cheese samples were within these permissible limits until end of refrigerated storage, while the higher levels of TBC (>10 5 cfu/g) were showed in control group. A significant reduction of psychrophilic counts in all treated cheese groups may attributed to effectivness of peptides in camel whey proteins hydrolysates mainly potent camel Lactoferricin peptides as demonstrated by Pirkhezranian et al (2020).…”
Section: Discussionmentioning
confidence: 80%
“…In this regards, Reyes-Cortes et al, (2017) showed that this chimeric peptide mediated its antibacterial activity by entering the cytoplasm through translocation across the bacterial membrane and possibly interacting with internal organelles [33]. Consistent with these results, Pirkhezranian et al, (2020 a, b) using molecular simulation analysis showed that cLFchimera and its derivatives had a higher a nity for DNA interaction and hypothesized this chimeric peptide mediated its activity by intramolecular mechanisms which interference DNA related pathways such as DNA replication [34,35]. However, treatment of all bacteria with antibiotics and their combinations (antibiotics + peptide) resulted signi cantly increased the release of cellular contents.…”
Section: Discussionmentioning
confidence: 82%